Instilling Religious Moderation in Early Childhood at Raudhatul Athfal Ponorogo: The Role of National Insight-Based Learning - Suryani, Lilis; Fatimah, Siti; Jarudin, Jarudin; Aarif, Mohd (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study explores the role of national insight-based learning in fostering religious moderation among young children. It investigates how early childhood education can serve as a vehicle for instilling values of tolerance, respect, and moderation among young children, thereby contributing to developing well-rounded, socially responsible citizens.Design/methods/approach – Qualitative research with a case study approach involving five Early Childhood Education (ECE) teachers from Raudhatul Athfal (RA) Muslimat NU 007 Gandu I Ponorogo, East Java, ten parents, and 30 children. Data were collected through classroom observations, teacher interviews, and surveys with parents to understand how national insight-based learning is integrated into early childhood education using a context-sensitive instrument, the Moderation Attitude Scale for Early Childhood (MASEC) and PERAMAH framework. Thematic analysis was used to identify key patterns and insights from the data. First, all recordings were transcribed verbatim and read repeatedly to ensure familiarity. Next, an open coding process was conducted, and illustrative quotes were selected. A thematic map was created to show the relationships between themes.Findings – The findings suggest that national insight-based learning significantly promotes religious moderation in children. Children demonstrated increased awareness of religious diversity and tolerance through culturally responsive teaching methods, such as stories, activities, and discussions rooted in national identity and values. Additionally, educators noted improvements in children's ability to engage with peers from different religious backgrounds with respect and empathy.Research implications/limitations – The research highlights the potential of early childhood education to play a crucial role in shaping children's religious attitudes. However, the study is limited by its small sample size and the short-term nature of the observation period. Further, longitudinal studies are recommended to assess the long-term impact of national insight-based learning on religious moderation across different educational settings.Practical implications – This study offers insights for early childhood educators and policymakers, highlighting the importance of integrating national insight-based learning and promoting inclusive teaching to foster early religious tolerance.Originality/value – This study presents a novel perspective on integrating national identity and religious moderation in early childhood education, addressing a theoretical gap and proposing a replicable NIBL-based model for value formation.Paper type Case study